PENDIDIKAN AGAMA ISLAM DALAM MENGATASI PERILAKU HOMOSEKSUAL (GAY) - Agung Alamsyah; Hasbiyallah Hasbiyallah; Nanat Fatah Natsir (Risâlah, Jurnal Pendidikan dan Studi Islam, 2019)
This study aims to explore and understand how the role of Islamic religious education in preventing and treating homosexual or gay behavior. Because there are so many homosexual actors who experience a psychological shock caused by their ignorance in dealing with the matter. The results of this study are to find out the extent to which homosexuals view the prohibition of Islam in carrying out such deviant behavior and also to find out how to overcome this deviant behavior with prevention and healing through the teachings of Islamic religious education. This study used a qualitative method with a phenomenological approach and also a study of religious studies as a solution in overcoming homosexual behavior and using five data sources in the form of five different gay resource persons. Homosexual informants realize that homosexual behavior is something that is prohibited and forbidden by religion and a way to overcome this behavior is as a prepentive effort by realizing the prohibition of this behavior in religion, leaving all associations related to homosexual behavior, realizing the danger posed by behavior homosexuals and provide counseling for Islamic understanding to homosexual actors while curative efforts that can be taken are by doing ruqyah syar'iyyah and also the rituals of the riyadhah of ibadah.